Implementation of Deep and Digital Learning Approaches to Teachers of Al-Mutmainna Islamic Boarding School to Enhance Pedagogical Competence for the Implementation of the SDGS of Quality Education - Arbi Batulante; Syafruddin; Nurhairunnisah; Paisatur Rahmi (Pascasarjana Universitas Mataram, 2025)
The goal of this PKM activity is to improve teachers' knowledge and skills in implementing deep learning and digital learning approaches. The method used in this activity is outreach, training, and mentoring for teachers at the Almutmainnah Islamic Boarding School in Leseng Village. This activity was carried out with the primary objective of enhancing teachers’ pedagogical competence so that they are able to design and implement learning in accordance with the demands of the 21st century. Through this program, teachers were not only introduced to the concept of deep learning, which emphasizes mastery of critical, creative, collaborative, and communicative skills, but also trained in the utilization of digital learning technologies that support more interactive and adaptive instruction.The implementation of this activity was divided into three main stages: preparation, implementation, and evaluation. The execution of this community service program (PKM) has successfully improved the pedagogical competence of teachers at Pondok Pesantren Al-Mutmainnah through the application of deep learning and digital learning. Based on the evaluation results, it was evident that most teachers experienced an increase in their understanding of designing deep learning-based instruction that fosters students’ critical, analytical, and creative thinking skills. In addition, teachers’ ability to operate digital learning applications (such as Canva, Quizizz, and Google Classroom) improved significantly. Teachers were also able to produce innovative digital learning products and became more confident in integrating technology into the classroom. Another achievement was the establishment of a teacher learning community, which serves as a platform for the sustainability of the program. This indicates that the PKM activity has generated positive and continuous impacts in supporting the achievement of SDG 4 (Quality Education).